LEGAL GROUNDS FOR CONCLUDING AGREEMENTS WITH FOREIGN ATHLETES - Aminov Botir Umidovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, analyze the legal basis for concluding agreements with foreign athletes